'A Test that is about Your Life': The Involvement of Refugee Children in Asylum Application Proceedings in the Netherlands. (2nd March 2022) - Rap, Stephanie
ABSTRACT: Refugee children are often neither recognised as rights holders nor as active agents in asylum procedures. A one-sided view of these children as vulnerable objects is not in coherence with international children's rights, including the UN Convention on the Rights of the Child, which regards all children as autonomous subjects and full bearers of rights. Through 21 in-depth interviews with unaccompanied, separated, and accompanied children in the Netherlands, their perceptions and experiences are collected and analysed in relation to their right to be informed and to participate in asylum application proceedings. It is shown that children possess little information on the asylum application interview, which they perceive as particularly stressful. However, they display agency in the choices they make during the interview. Accompanied children find themselves in a rather difficult position, feeling jointly responsible for the outcome of the procedure. It is concluded that effective and meaningful participation, in line with the international children's rights framework, is difficult to realise in the context of asylum proceedings.